2021
DOI: 10.1101/2021.07.13.21260484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Comparison of Three Real-Time PCR Kits for Sars-Cov-2 Diagnosis Reveals Discrepancies on the Identification of Positive Covid-19 Cases and Dispersion on the Values Obtained for the Detection of Sars-Cov-2 Variants

Abstract: The COVID-19 pandemic has generated a huge challenge and threat to public health throughout the world population. Reverse transcription associated with real-time Polymerase Chain Reaction (RT-qPCR) has been the gold-standard molecular tool for diagnosis and detection of the SARS-CoV-2. Currently, it is used as the main strategy for testing, traceability, and control of positive cases For this reason, the on-top high demand for reagents has produced stock-out on several occasions and the only alternative to kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In both samples, the RNase P amplification was quite similar (Cq = 16.82; Cq = 16.75, respectively) ( Figure 1(b) ). The detection limit for ORF1ab, as considered by our laboratory and described previously [ 14 ], confirmed the positive diagnosis for COVID-19 for both samples. The phylogenetic analysis showed that 0606-201 and 0308-063 samples were members of Nextstrain clades 20B and 20A, respectively ( Figure 1(c) ).…”
Section: Resultssupporting
confidence: 80%
“…In both samples, the RNase P amplification was quite similar (Cq = 16.82; Cq = 16.75, respectively) ( Figure 1(b) ). The detection limit for ORF1ab, as considered by our laboratory and described previously [ 14 ], confirmed the positive diagnosis for COVID-19 for both samples. The phylogenetic analysis showed that 0606-201 and 0308-063 samples were members of Nextstrain clades 20B and 20A, respectively ( Figure 1(c) ).…”
Section: Resultssupporting
confidence: 80%
“…In diagnosis, it is a solid basis to validate the proper process of total RNA extraction and subsequent amplification of the SARS-CoV-2 genes of interest used (ORF1ab, N, S, E , and RdRp). Due to the nonamplification of an internal gene, the results may be invalidated [ 19 ].…”
Section: Discussionmentioning
confidence: 99%